PERBANDINGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE TIPE TALKING STICK DENGAN MODEL PEMBELAJARAN TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 9 KOTA JAMBI - Pratiwi Indah Sari, Rizki Amaliah (Universitas Batanghari Jambi, 2017)
This study aims to find out how the results of student learning using the learning model of talking stick and make a match learning model on economic subjects of capital market subject in class XI IIS SMA Negeri 9 Kota Jambi. The results showed student learning outcomes in class XI IIS 5 on the subject of capital market capital economics at SMA Negeri 9 Kota Jambi at the time of pre-test using the learning stick talking model obtained the highest learning result of 55.00, while using model make a match of 67.50. This means the pre-test when using make a match is higher than the talking stick learning model. Meanwhile, at the time of post-test using the talking stick learning model obtained the highest learning result of 50.00. Meanwhile, using make a match model of 77.50. This means the pre-test when using make a match is higher than the talking stick learning model.Kata Kunci : Learning Model, Talking Stick, Make a Match.